Results of Vertebral Augmentation Treatment for Patients of Painful Osteoporotic Vertebral Compression Fractures: A Meta-Analysis of Eight Randomized Controlled Trials - Li, Lianhua; Ren, Jixin; Liu, Jia; Wang, Hao; Wang, Xiaowei; Liu, Zhi; Sun, Tiansheng (PloS one, 2015)
In 2009 two RCTs were publicated to question the efficacy of vertebroplasty comparing with sham treatment (ST) in the New England Journal of Medicine (NEJM), which provoked an academic debate on the efficacy of PVA. The purposes of our study were to compare clinical differences in pain relief, spinal functional outcomes, and overall quality of life between PVA and CT for painful osteoporotic VCFs. We searched PubMed, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials and Web of Knowledge from January 1980 to June 2013 with Medical Subject Headings terms and keywords. Risk of bias in the included studies was assessed in accordance with the Cochrane risk of bias tool. In this Meta-analysis dichotomous and continuous variables were calculated using the risk ratio (RR) and standardized mean difference (SMD), respectively. Eight studies involving 987 patients met the criteria for inclusion. The VAS SMD was favoring the experimental group significantly (p < 0.001). Subgroup analysis suggested that the patients performed PVA with mean fracture age less than 3 months would got pain relief earlier and more durable than the control group (P <0.05). The SMD of spinal function assessed with RDQ and Oswestry LBP data was in favor of the experimental groups. QOL outcome improvement was demonstrated statistically significant at early, middle and late-term follow-up for PVA than the control group (P <0.05). In conclusion, this meta-analysis, which evaluated PVA for osteoporotic VCFs, demonstrated significant improvement regarding VAS, spinal function and QOL outcomes. The optimal fracture age was less than 12 weeks.